PENGEMBANGAN POTENSI IKAN CEMPEDIK DI BELITUNG TIMUR: SUATU PENDEKATAN BIOLOGIS DAN ETNOBIOLOGI - Yulian Fakhrurrozi; Ardiansyah Kurniawan; Andri Kurniawan (Fakultas Biologi | Universitas Jenderal Soedirman, 2016)
Fish Cempedik has become a freshwater entity in East Belitung District. The abundance of Cempedik is almost used by people in rainy season, by catching activity in downstream of Lintang River and Lenggang River that disembogue in Bendungan Pice. The actvity, however, is not done in dry season caused Fish Cempedik is very difficult to found there. This research aim is to exlore Fish Cempedik’s existence by study of biology and ethnobiology approach, as a development activity of freshwater potential in East Belitung District, especially Fish Cempedik. The results show Fish Cempedik has morphology similarities that indicate group of Family Cyprinidae, there is a round dark spot on its caudal peduncle, silver skin, forked shape caudal fin, two barbels on each side of mouth, 1,8-3,6 g in weight, total lenght 5,13-6,36 cm, standard lenght 3,89-5,07 cm, head lenght 0,69-1,16 cm, head height 0,47-0,9 cm, body height 0,83-1,46 cm, caudal peduncle height 0,31-0,78 cm, caudal peduncle length 0,59-0,95 cm, body wide 0,42-0,9 cm, 21 caudal spines, 12 dorsal spines, 6 anal spines, and 9 ventral spines on each side. In fish catching, people use bubu or sero, many arrested during the rainy season, and in the dry season are more common in the upstream than downstream.